Exploration of Variation in E-Recruitment Content of Indian Firms - Matlani, Heena (2009)
This study is concentrating on the Indian Companies to discover the various factors that explain the dissimilarity in the E-recruitment content . A qualitative approach was used to conduct this research in order to gain insights in the recruitment tactics of the firms. Since the purpose was to study why the recruitment descriptions on the corporate websites differ between firms, document analysis was used as a method of collecting data from the corporate websites. Purposive Sampling was used to select a sample of top 50 Indian firms from a list of Top Indian companies. The research identified eight recruitment variables that were studied in the career section of the sample firms. Further, the data was analyzed using simple descriptive analysis. The study revealed five factors responsible for the dissimilarity between the recruitment content of the sample firms. These are – size of the firm, age of the firm, the type of job, extent to which the firm pursues employer branding and the industry to which it belongs. Findings suggest that the industry of the firm is the most crucial factor influencing the recruitment content on the corporate websites. Banking and Metals and Mining Industry provide least recruitment information on their websites. Thus, overall the study provides a comprehensive understanding of the online recruitment strategies and content of the Indian firms.